Designing a Peptide‐modified Screen‐printed Gold Electrode as a Sensor for the Human Monocytic Leukemia Cell Line. Issue 3 (25th August 2022) - Kodaira, Keito; Kuramitz, Hideki; Sugawara, Kazuharu
Abstract: We designed a screen‐printed gold electrode (SPGE) with a peptide to detect cancer cells. The ability to sense circulating tumor cells (CTCs) and monitor their movement in blood vessels is important for cancer diagnosis. Human monocytic leukemia cells were selected as a model of CTCs because of their origin. The cell‐recognition and cell‐sensing peptide moieties were EICADP and Y4 C. The SPGE was modified with the cell‐recognition moieties of the CY4 EICADPY4 C in a bridge‐type construction due to the cysteine residue at both terminals. The calibration curve was linear and ranged from 25 to 2, 000 cells/mL with a LOD of 8 cells/mL. Abstract :